The Effect of Organizational Climate on Organizational Citizenship Behavior (OCB) Through Work Engagement as an Intervening Variable: A Case Study of Employees of the Regional Office of the Directorate General of Treasury of South Kalimantan Province - Sofwati, Nely Noer; Meiske Claudia; Aprianti (Open Access Indonesia Journal of Social Sciences, 2023)
This research was conducted to analyze the effect of organizational climate on organizational citizenship behavior (OCB), with work engagement as an intervening variable. The phenomenon is that many employees lack discipline in fingerprinting, so they are required to pay more attention to attendance lists to achieve good organizational goals. The research sample was 42 people who were all employees of the Regional Office of the Directorate General of Treasury of South Kalimantan Province. Data collection was carried out through a questionnaire with the aim of providing an assessment of the organizational climate (X), to test how well the level of employee engagement is at work (Z), and to measure how big the OCB of employees is in the organization. (Y). The data analysis method used is partial least square (PLS) version 4.0. The results showed that organizational climate had no significant effect on organizational citizenship behavior (OCB), while organizational climate had a significant positive effect on work engagement, then work engagement had a positive and significant effect on organizational citizenship behavior (OCB). Furthermore, the organizational climate has a positive and significant effect on employee organizational citizenship behavior (OCB), both indirectly through the intervening variable, namely work engagement.